Biobutanol production from sugarcane bagasse by Clostridium beijerinckii strains. (21st January 2020) - Narayanasamy, Saraswathi; Chan, Kit Lun; Cai, Hui; Abdul Razak, Ahmad Hilman Bin; Tay, Boon Keat; Miao, Huang
Abstract: Acetone–butanol–ethanol (ABE) fermentation was performed with sugarcane bagasse (SCB) hydrolysate using Clostridium beijerinckii strains. A cost‐effective SCB medium was developed with no enzymatic hydrolysis and no supplementation of extra carbon source or expensive nitrogen source. One of the C. beijerinckii strains studied was able to produce butanol with butanol productivity of 1.23 g/L/day with butanol yield of 0.18 g/g of sugars from the developed medium. High utilization rate of both glucose and xylose was observed in SCB medium during ABE fermentation. This study shows that SCB is a promising substrate for cellulosic biobutanol production. Abstract : A cost‐effective sugarcane bagasse (SCB) medium was developed with lower energy and chemical usage, and with no addition of expensive nutrients. The SCB medium was able to support butanol production by Clostridium beijerinckii strains with satisfactory sugar utilization rate. The SCB medium could also be potentially used for production of other value‐added chemicals.